Comparing Effectiveness of Hay Infusion and Sugar Fermentation Solution as Ovitrap's Attractans to Aedes aegypti - Nastiti Widoretno (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2018)
Dengue Hemorrhagic Fever (DHF) is still one of the major public health problems in the world and Indonesia. There are several methods of mosquito vector control, one of them is the use of ovitrap and the addition of attractants which is a compound that may attract gravid mosquitoes to lay eggs. Some examples of attractants are hay infusion and sugar fermentation solution. This research aimed to compare effectiveness of hay infusion  and sugar fermentation solution as Aedes aegypti attractants. This research type was true experimental laboratory with complete randomized design which is divided into 3 groups of ovitrap containing aquades as control, 20% hay infusion and 20% sugar fermentation solution. Ovitraps with those attractants were put into a mosquito coop containing 25 gravid female mosquitoes. Mosquito’s eggs counting was done after 2 days with 9 times repetition. The data were then analyzed using Kruskal-Wallis and Mann-Whitney test. It was found that the difference of mosquito’s eggs number in the ovitrap containing the fermentation solution of sugar and hay infusion had a significance value of 0.000 (p> 0,05). It means that hay infusion is more effective compared with sugar fermentation. Keywords                   : DHF, ovitrap, attractant, hay infusion, sugar fermentation solution